Induction of Browning in White Adipocytes: Fucoidan Characterization and Gold Nanoparticle Synthesis from Undaria pinnatifida Sporophyll Extract - Sun Young Park; Kangmin Park; Hye Mi Kang; Woo Chang Song; Jin-Woo Oh; Young-Whan Choi; Geuntae Park (Marine Drugs, 2023)
Seaweed extracts and their specific polysaccharides are widely known for their ability to act as reducing and capping agents during nanoparticle synthesis. Their application is highly favored in green synthesis methods, owing to their eco-friendliness, cost-effectiveness, and remarkable time and energy efficiency. In this study, fucoidan extracted from Undaria pinnatifida sporophyll (UPS) is introduced as a polysaccharide that effectively serves as a dual-function reducing and capping agent for the synthesis of gold nanoparticles (AuNPs). Results from various analyses indicate that AuNPs derived from UPS extract display a uniform spherical shape with an average size of 28.34 ± 1.15 nm and a zeta potential of −37.49 ± 2.13 mV, conclusively confirming the presence of Au. The FT-IR spectra distinctly revealed the characteristic fucoidan bands on the stabilized UPS-AuNPs surface. A 1H-NMR analysis provided additional confirmation by revealing the presence of specific fucoidan protons on the UPS-AuNPs surface. To comprehensively evaluate the impact of UPS extract, UPS-AuNPs, and fucoidan on the biological properties of adipocytes, a rigorous comparative analysis of lipid droplet formation and morphology was conducted. Our findings revealed that adipocytes treated with UPS extract, fucoidan, and UPS-AuNPs, in that order, exhibited a reduction in the total lipid droplet surface area, maximum Ferret diameter, and overall Nile red staining intensity when compared to mature white adipocytes. Furthermore, our analysis of the effects of UPS extracts, UPS-AuNPs, and fucoidan on the expression of key markers associated with white adipose tissue browning, such as UCP1, PGC1a, and PRDM16, demonstrated increased mRNA and protein expression levels in the following order: UPS-AuNPs > fucoidan > UPS extracts. Notably, the production of active mitochondria, which play a crucial role in enhancing energy expenditure in beige adipocytes, also increased in the following order: UPS-AuNPs > fucoidan > UPS extract. These findings underscore the pivotal role of UPS extract, fucoidan, and UPS-AuNPs in promoting adipocyte browning and subsequently enhancing energy expenditure.